Peran CSR Perusahaan Konstruksi dalam Peningkatan Ketahanan Air Masyarakat: Studi Pemenuhan Air Bersih RW 02 Sumurboto - Agnes Galih Praditajati; Nectaria Putri Pramesti (Jurnal Atma Inovasia, 2026)
The availability of clean water is a vital need for health and quality of life; however, access in Indonesia remains uneven. This study aims to examine the role of Corporate Social Responsibility (CSR) programs from construction companies in strengthening clean water distribution infrastructure as an effort to enhance community water resilience. The service method was carried out in a participatory manner by involving the residents of RW 02, Sumurboto Sub-district, the local government, and construction company “X.” Activities included drilling a ±50-meter-deep well, constructing a 3,000-liter water tower, building a pump house, and installing a pipeline distribution system to serve approximately 300 households. The results show that this initiative succeeded in expanding more equitable access to clean water, reducing diseases caused by contaminated water, and easing household financial burdens. In addition, infrastructure management training encouraged community independence in maintaining the facilities. Technical challenges, such as the lack of local expertise and installation issues, were resolved through cross-stakeholder coordination. In conclusion, collaboration between the construction company, government, and community through CSR schemes proved effective in providing clean water access while strengthening community self-reliance toward sustainable water resilience.